Pengaruh Advertising Instagram Dan Suasana Toko Terhadap Minat Beli : (Survei Pada Konsumen Sakka.Id Tasikmalaya) - Sindi Oktasari (CV. ULIL ALBAB CORP, 2022)
This study aims to determine the effect of Instagram advertising and store atmosphere partially on buying interest at Sakka.id Tasikmalaya. The type of research used is quantitative research with causality method and survey approach. Sampling using non-probability sampling that is purposive sampling as many as 100 respondents, the data was obtained using a questionnaire and then the data was analyzed using multiple linear regression analysis techniques. The results of this study indicate that Instagram Advertising is in the high category, the store atmosphere is in the high category and the intention to buy at Sakka.id Tasikmalaya is in the high category. Instagram advertising and store atmosphere affect buying interest at Sakka.id Tasikmalaya.